Efficient and Robust NK-Cell Transduction With Baboon Envelope Pseudotyped Lentivector - Colamartino, Aurelien B. L.; Lemieux, William; Bifsha, Panojot; Nicoletti, Simon; Chakravarti, Nitin; Sanz, Joaquín; Roméro, Hugo; Selleri, Silvia; Béland, Kathie; Guiot, Mélanie; Tremblay-Laganière, Camille; Dicaire, Renée; et al. (Frontiers in Immunology, 2019)
NK-cell resistance to transduction is a major technical hurdle for developing NK-cell immunotherapy. By using Baboon envelope pseudotyped lentiviral vectors (BaEV-LVs) encoding eGFP, we obtained a transduction rate of 23.0±6.6% (mean±SD) in freshly-isolated human NK-cells (FI-NK) and 83.4±10.1% (mean±SD) in NK-cells obtained from the NK-cell Activation and Expansion System (NKAES), with a sustained transgene expression for at least 21 days. BaEV-LVs outperformed Vesicular Stomatitis Virus type-G (VSV-G)-, RD114- and Measles Virus (MV)- pseudotyped LVs (p<0.0001). mRNA expression of both BaEV receptors, ASCT1 and ASCT2, was detected in FI-NK and NKAES, with higher expression in NKAES. Transduction with BaEV-LVs encoding for CAR-CD22 resulted in robust CAR-expression on 38.3%±23.8% (mean±SD) of NKAES cells, leading to specific killing of NK-resistant pre-B-ALL-RS4;11 cell line. Using a larger vector encoding a dual CD19/CD22-CAR, we were able to transduce and re-expand dual-CAR-expressing NKAES, even with lower viral titer. These dual-CAR-NK efficiently killed both CD19KO- and CD22KO-RS4;11 cells. Our results suggest that BaEV-LVs may efficiently enable NK-cell biological studies and translation of NK-cell-based immunotherapy to the clinic.